Analysis of acceptance and use of the NCX application using the UTAUT2 modification model at Telkom Indonesia - Hadi, Fikrian; Noviaristanti, Siska (International Journal of Accounting and Management Information Systems, 2024)
Purpose: This study aims to examine user evaluations of factors influencing the use of the NCX application and their impact on behavioral intention and usage. Using the modified UTAUT2 model, the study focuses on Telkom CFU Enterprise, which delivers ICT services such as connectivity, cloud, and digital platforms. NCX, a CRM application, supports CFU Enterprise operations. Method: This application can be used to manage the customer data. This study uses the modified UTAUT2 model, which is a development of the UTAUT2 model that adds compatibility and personal innovativeness constructs. Results: This study is expected to provide useful insights to increase the adoption and use of the NCX application in the Telkom CFU Enterprise environment. Conlusion: Key variables from the modified UTAUT2 model, including compatibility and personal innovativeness, significantly affect user intention and behavior, providing guidance for improving NCX engagement. Limitation: The research is limited to the CFU Enterprise environment and may not be generalizable to other units or industries. The use of cross-sectional data also restricts the ability to observe behavioral trends over time. Contribution: This study contributes to the extension of UTAUT2 by validating additional constructs in a corporate CRM context. It also offers practical recommendations for improving technology acceptance within enterprise environments through strategic alignment with user needs and characteristics.